Results and predictive factors for single level L4-5, and L5-S1 disc herniation surgery - Rasheed, Saad Mubarak; Ali, . Ali Aziz; Al-Mubarek, Hussein (AL-Kindy College Medical Journal, 2015)
Background: The disc prolapse is a common condition especially in young adults. Different levels are affected in the lumber region; the L4/L5 disc is more susceptible to longitudinal load and is the most common site of lumbar disc prolapse. The L5/S1 disc is protected from torsion load by strong ilio-lumbar ligaments but it is more susceptible to axial compressive forces. Many factors affect the result and outcome of surgery in these levels.Objective: The aim of this study is to correlate operative data, short-term results, complications, and prognostic factors (age, gender, mobility, hospital stay, and level of pain) for one-level lumber discectomybetween different levels (L4–L5 vs. L5–S1).Methods In this prospective study, 32 patientsin Al-Yarmouk teaching hospital undergoing survey form March 2008-December 2012.Six patients were excluded from this study because they were diabetics and multilevel disc degeneration .Fifteen (57.6%) patients undergoL5-S1 discectomy and 11 (42.4%) patients undergoL4-5 discectomy. Questionnaires for leg and back pain intensity (Visual Analogue Scale ;VAS), duration of leg pain, and disability (Oswestry Disability Index; ODI), were obtained preoperatively, 3 months, 6 months, 1-year- and 2 year follow-up.Analyses were utilized to evaluate the relationship between surgical outcomes and variable (gender, age, lumber segment, pre-operative ODI, and pre-operative VAS).Results: Mean operative time was[73.44 ± 26.25] min, mean hospital stay was [3-7] days, and mean mobilitywas [2.55 ± 0.93] days. At 2-year follow up, patients revealed a statistical significant improvement inVAS pain (P < 0.05), and ODI lumbar function (P < 0.05).The complications rate were 20.3 %.Our study elaborates good results for one-segmental L5-S1overL4-L5 discectomy. Discectomy of the L4–L5 disc wasassociated with an increased risk of complication (P < 0.05). The comparison revealed that operative time was influenced by age (P = 0.034); hospital stay was influenced by level (P = 0.036) and pre-op VAS (P = 0.006); while complications were influenced by level (P = 0.001) and pre-op ODI (P = 0.049Conclusion: The study revealed significant results for L5-S1 discectomy over L4-L5 discectomy in the late follow up period; the complications rate were higher in L4-L5 level discectomy